Radioiodinated N-(alkylaminoalkyl)-substituted 4-methoxy-, 4-hydroxy-, and 4-aminobenzamides: biological investigations for the improvement of melanoma-imaging agents - Mohammed, Ashour B.; Nicholl, Ciaran; Titsch, U.; Eisenhut, Michael (Nuclear medicine and biology, 1997)
The synthesis and radiolabeling of 27 new N-(alkylaminoalkyl)-4-methoxy-, 4-hydroxy-, and -4-aminobenzamides are described and evaluated in C57Bl/6 mice with subcutaneously transplanted B16 melanoma in order to screen the optimal chemical structure for melanoma scintigraphy. Using Tl(TFA)3 for 131I− labeling, a series of radioiodinated 4-methoxy benzamide derivatives proved to exhibit superior melanoma uptake with outstanding melanoma/non-target-tissue ratios. From the benzamide derivatives tested, N-(2-(1′-piperidinyl)ethyl)-3-[131I]iodo-4-methoxybenzamide (1) and N-(2-diethylaminoethyl)-3-[131I]iodo-4-methoxybenzamide (2) demonstrated best results. The introduction of 4-hydroxy and 4-amino groups led to less favourable benzamides. While the former compounds showed little melanoma uptake, the latter revealed unfavourable melanoma/non-target-tissue ratios. Additionally, it could be shown that an amino group was inevitably necessary for melanoma uptake, and that dialkylation of the amide nitrogen and replacing CONH by CH2NH revealed less advantageous results.
Elektronische Reproduktion der Druck-Ausgabe 24. Dezember 2002
Gesehen am 09.12.2024